Usborne Phonics Readers : Llamas in Pyjamas - Russell Punter (London, United Kingdom Usborne Publishing Ltd, 2014)
This title tells a lively story with humourous illustrations, ideal for children who are beginning to read for themselves, or for reading aloud together. The book features simple rhyming text and phonic repetition which is specially designed to develop essential language and early reading skills.
Keywords: PY - Language